Advancing Alternatives Assessment for Safer Chemical Substitution: A Research and Practice Agenda. (4th October 2018) - Tickner, Joel; Jacobs, Molly; Malloy, Tim; Buck, Topher; Stone, Alex; Blake, Ann; Edwards, Sally
ABSTRACT: Alternatives assessment has emerged as a science policy field that supports the evaluation and adoption of safer chemistries in manufacturing processes and consumer products. The recent surge in the development and practice of alternatives assessment has revealed notable methodological challenges. Spurred by this need, we convened an informal community of practice comprising industry experts, academics, and scientists within government and nongovernmental organizations to prioritize a research and practice agenda for the next 5 years that, if implemented, would significantly advance the field of alternatives assessment. With input from over 40 experts, the agenda outlines specific needs to advance methods, tools, and guidance in 5 critical areas: hazard assessment, comparative exposure characterization, life cycle considerations, decision making, and professional practice. Fifteen research and practice needs were identified, ranging from relatively simple efforts to define a minimum hazard data set to the development of more complex performance and decision‐analytic methods and data integration tools. Some research needs involve adapting existing approaches to the alternatives assessment context, while others will require the development of entirely new methods and tools. The proposed research and practice agenda is ambitious. Implementing it will require expanding the current network of researchers from academia, government, and industry, as well as increased funding for methodological, application, and evaluation research. Integr Environ Assess Manag 2018;00:000–000. © 2018 SETAC Key Points: Alternatives assessment (AA) is experiencing "growing pains" as the demand for safer chemicals, materials, and products and the development of a variety of tools and methods outpace the establishment of standardized approaches and a coherent research and practice agenda. To advance consistency and growth in the application of AA in science policy, 15 research and practice needs are identified, ranging from efforts to define a minimum hazard data set to the development of performance and decision‐analytic methods and data integration tools. Methods development efforts for AA should support comprehensive, yet efficient, approaches for the informed substitution of hazardous chemicals, considering the variety of decision contexts in which it is used: regulation, business operations, green chemistry, and engineering development. Implementing this research and practice agenda will require dedicated funding, education, and training and the establishment of a more formalized, interdisciplinary community of practice to develop and apply new approaches and share best practices.